Hubungan Antara Persepsi Terhadap Kompensasi Finansial Dengan Kinerja Karyawan Pada PT. Bank Negara Indonesia (Persero), Tbk (Kantor Cabang Slamet Riyadi Surakarta) - Maulani, Octhavera Putri, Drs. Mohammad Amir, M.Si (2016)
Achieving high performance is not an easy thing to do for employee. This can be seen on low performance employee that is caused by the low perceptions on financial compensation so that the employee is unable to fulfill daily needs. Therefore, the employee is expected to have high perceptions on financial compensation in order to decrease the performance related to company achievement. This research is aimed to know the relation between perceptions against financial compensation on employee performance, perceptions level on financial compensation and employee performance level. Hypothesis that is submitted is the positive relation between perceptions against financial compensation on employee performance. The method used on this research is quantitative, with 80 outsourcing employees of PT Bank Negara Indonesia (Persero), Tbk. (Slamet Riyadi Branch Office Surakarta) as the research subject. Data collecting method used is perceptions scale on financial compensation and employee performance scale. The data collecting technique used is sampling quota while data analysis technique used is product moment. Product Moment correlation coefficient (rxy) of 0,705 ; with significance (p) = 0,000 (p > 0,01), that there is a significant positive relationship between perceptions of financial compensation with employee performance. The effective contribution of these two variables is shown by the determinant coefficient (r2) = 0,497 which shows that perceptions of financial compensation affects employee performance amounted to 49,7% and 50,3% were influenced by other variables. Subjects in this study had a perception of the level of financial compensation being the empirical mean and mean of = 101,51 hypothetical at = 100, the subject also has the performance of employees with an empiric average of = 126,62 and hypothetical average of = 110.